2007
DOI: 10.1144/1354-079306-733
|View full text |Cite
|
Sign up to set email alerts
|

Faulting and fault sealing in production simulation models: Brent Province, northern North Sea

Abstract: Faults can severely compartmentalize pressures and fluids in producing reservoirs, and it is therefore important to take these effects into account when modelling field production characteristics. The Brent Group fields, northern North Sea, contain a complex arrangement of fault juxtapositions of a well-layered sand-shale reservoir stratigraphy, and fault zones containing a variety of fluid flow-retarding fault rock products. It has been our experience that these fault juxtapositions impact the ‘plumbing’ of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 54 publications
2
75
1
Order By: Relevance
“…In reality though, faults are narrow zones or volumes of highly and heterogeneously strained rocks, with petrophysical properties differing from those of the host rock. Internal fault structure varies throughout reservoirs (Fisher and Jolley, 2007;Jolley et al, 2007;Faulkner et al, 2010 and references therein). Fault structure and distribution of fault properties depend on factors such as host lithology and stratigraphy (Davatzes and Aydin, 2005;Bastesen and Braathen, 2010), depth of burial at time of faulting (Fisher and Knipe, 2001), initial fault array geometry and structural evolution (Childs et al, 2009), and diagenesis (Solum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In reality though, faults are narrow zones or volumes of highly and heterogeneously strained rocks, with petrophysical properties differing from those of the host rock. Internal fault structure varies throughout reservoirs (Fisher and Jolley, 2007;Jolley et al, 2007;Faulkner et al, 2010 and references therein). Fault structure and distribution of fault properties depend on factors such as host lithology and stratigraphy (Davatzes and Aydin, 2005;Bastesen and Braathen, 2010), depth of burial at time of faulting (Fisher and Knipe, 2001), initial fault array geometry and structural evolution (Childs et al, 2009), and diagenesis (Solum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Needham et al, 1996;Childs et al, 1997;Jolley et al, 2007). A number of studies have utilised 2D seismic forward modelling to generate synthetic seismic across known geometries and facies distributions (Johansen et al, 1994;Hodgetts and Howell, 2000;Alaei and Petersen, 2007) however, few if any use the technique to illustrate the potential uncertainties pertinent to hydrocarbon exploration as described here.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it can be shown that, for clay mineral contents > 25 wt.-%, K reduces to values < 10 -9 m/s, and for clay mineral contents of > 40 wt.-% to values of < 10 -11 m/s. Jolley et al (2007) compiled data from a large number of permeability tests on fault rock in cores from a large K depth range from the Brent Province (North Sea) as a function of clay mineral content. All samples with clay contents > 40 wt.-% yielded K values Ä 10 -12 m/s (original permeability data transferred into hydraulic conductivity values, see Nagra 2014b, Dossier VI, Fig.…”
Section: Comparison With Data From Other Clay Rocksmentioning
confidence: 99%